Abstracts of the 47th Annual Conference of Young Scientists ‘Cold in Biology and Medicine. Current Issues in Cryobiology, Transplantology and Biotechnology’ May 23, 2023, Kharkiv, Ukraine - Problems of Cryobiology; Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):280-282